Implementing Circular Economy Model In Rural Eco-tourism: A Case Study From Bandung - Dwi Wiryawan, I Gusti Ngurah; Kusdibyo, Lusianus; Rafdinal, Wahyu; Septyandi, Chandra Budhi (Integrasi Sains Media, 2025)
This study examines the implementation of the Circular Economy Business Model (CEBM) in rural eco-tourism through a case study of Cikahuripan Village, Bandung. It explores how circular economy principles can support environmental sustainability, improve waste management, and enhance local economic resilience amid infrastructural, financial, and technological limitations. A qualitative approach was employed using in-depth interviews and focus group discussions involving community leaders, tourism actors, and policymakers. The findings highlight three major barriers, namely ineffective waste handling, weak financial mechanisms to sustain recycling initiatives, and low adoption of digital tools. These constraints undermine the viability of community-based eco-tourism efforts. The study recommends improving infrastructure, providing incentives for eco-friendly enterprises, and expanding digital literacy. Strengthening multi-stakeholder collaboration and encouraging visitor participation in conservation activities are also essential for fostering sustainable tourism in rural areas.